Enhanching Gamer Loyalty: Role of Immersiveness and Parasocial Relationship with NPC Characters in Narrative Games - Gatum Ananta Putra; Masmira Kurniawati (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study aims to examine how game experience influences player loyalty through immersiveness and parasocial relationships in digital games. Grounded in parasocial interaction theory, this study proposes that game experience enhances immersion and parasocial relationships, which in turn strengthen game loyalty. Research Method: This study employed a quantitative research design using a structured questionnaire distributed through Google Forms and the Kudata platform. The sample consisted of 285 active players of Genshin Impact, Wuthering Waves, and Honkai: Star Rail. The variables examined include game experience, immersiveness, parasocial relationships, and game loyalty. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 31 to test the proposed relationships among variables. Results and Discussion: The findings indicate that game experience does not have a significant direct effect on game loyalty. However, game experience significantly influences immersiveness and parasocial relationships. Immersiveness significantly affects both parasocial relationships and game loyalty, while parasocial relationships have a strong positive effect on game loyalty. These results suggest that player loyalty is shaped indirectly through immersiveness and parasocial relationships, indicating a full mediation mechanism. Implications: Game developers should enhance immersive, character-driven experiences to foster emotional attachment and long-term player loyalty. Originality: This study extends parasocial interaction theory by integrating immersiveness and parasocial relationships as mediating mechanisms in explaining digital game loyalty.